0318 "Oh, what sights to behold in this church turned upside down" - Eva L.E. Janssens (RIHA Journal)
This article focusses on a unique anti-Catholic illustrated broadsheet, De Rhoemse Kercke, from the Netherlands. Inscriptions with the initials of the makers corroborate that it was engraved by Robert Baudous (ca. 1574/75–1659) and published by Jacques de Gheyn II (1565–1629) in 1605. The engraving is accompanied by a poem long presumed lost. Commenting on the numerous pictured Catholic clergymen engaged in various abominable practices, this poem provides a unique glimpse into the thinking of its spin doctor – it is attributed to the theologian and emblematist Paulus de Kempenaer (Brussels, ca. 1554 – The Hague, 1618?). By analysing the iconography in relation to de Kempenaer's poem, this comprehensive study aims to unravel the purpose and intended audience of De Rhoemse Kercke.